Assessment of corporate governance quality in an enterprise - Xianfeng, Xie (Харківський національний автомобільно-дорожній університет, 2024)
In this qualification work, the concept, composition and types of corporate governance were considered. The key elements and approaches to its definition are considered. The process of implementing the enterprise strategy is considered. Generalized studies of the quality of corporate governance are considered. A point-rating assessment of the quality of corporate governance has been formed. The preconditions for the formation of corporate conflicts in the context of key groups of participants are considered. A point assessment of the potential for solving and preventing corporate conflicts is considered. An assessment of the corporate governance rating has been developed, it contains a component that will assess the subjective composition of participants in corporate relations. Projected assumptions regarding the development of the object of study are the growth of the corporate governance rating of the enterprise from the stage of development to the stage of stable.
Keywords: quality; corporate governance; ratings; efficiency; strategy